The Significance of Organizational Citizenship Behavior (OCB) Improving the Farmer Economy with Government Budget in Agricultural Sector - Sapar, Sapar; Harahap, Burhanuddin (Jurnal Penyuluhan Pertanian, 2025)
Government assistance through budget support and subsidies for the agricultural sector is very urgent because the agricultural industry functions as a support or fundamental foundation of the state in terms of meeting the basic needs of the Indonesian people, namely in Sustainable Development Goals (SDGs) No. 2, namely zero hunger. Agricultural development is an important and strategic venture that plays an important role in increasing productivity for Organizational Citizenship Behavior (OCB). Budgeting efforts are essential for the advancement of the agricultural sector and the improvement of agricultural management. This study aims to ensure a structure that can be applied to evaluate whether OCB directly or indirectly impacts the economic value of farmers in Palopo City by increasing the government budget in the agricultural sector. The methodology of this study integrates quantitative analysis with descriptive and inferential statistical analysis. Data was analyzed using inferential statistics using Structural Equation Modeling (SEM) techniques using the SmartPLS application. The results of the study show that OCB has a significant effect on agricultural budgeting, agricultural budgeting has a significant effect on improving farmers' economy, OCB has a significant effect on improving farmers' economy, and indirect effects of OCB have a significant effect on improving farmers' economy through agricultural budgeting. The use of research techniques with SEM analysis shows that agricultural budgeting is a significant mediating variable between OCB and the improvement of farmers' economies. In practical terms, this research provides the basis that interventions on organizational behavior and budget governance can be an operational strategy to achieve SDGs target No. 2 (zero hunger) at the local level.